2012
DOI: 10.1021/cb200439z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Influenza Endonuclease Inhibitors Using a Novel Fluorescence Polarization Assay

Abstract: Influenza viruses have been responsible for the largest pandemics in the previous century. Although vaccination and prophylactic antiviral therapeutics are the primary defense against influenza virus, there is a pressing need to develop new antiviral agents to circumvent the limitations of current therapies. The endonuclease activity of the influenza virus PAN protein is essential for virus replication and is a promising target for novel anti-influenza drugs. To facilitate the discovery of endonuclease inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 62 publications
0
69
1
1
Order By: Relevance
“…Structural studies have now revealed new opportunities for drug discovery that target the essential endonuclease activity of the virus (24)(25)(26). In the current study, we had two primary goals; to confirm that the known endonuclease inhibitor L-742,001 targets the enzyme within the intact virus by generating resistant mutants, and to survey the resistance potential of the endonuclease by characterizing the sites of mutation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural studies have now revealed new opportunities for drug discovery that target the essential endonuclease activity of the virus (24)(25)(26). In the current study, we had two primary goals; to confirm that the known endonuclease inhibitor L-742,001 targets the enzyme within the intact virus by generating resistant mutants, and to survey the resistance potential of the endonuclease by characterizing the sites of mutation.…”
Section: Discussionmentioning
confidence: 99%
“…S5A shows the full kinetic analysis from which V max and K M values of 3764190 s −1 and 1566 nM, respectively, were derived. We then measured the binding of our fluorescent probe (25) to PA N ΔLoop by fluorescent polarization, and the K d was found to be 44 nM (Fig. 3B).…”
Section: δLoopmentioning
confidence: 99%
See 1 more Smart Citation
“…Another endonuclease inhibitor identified by these investigators is flutimide, a fully substituted 1-hydroxy-3H-pyrazine-2,6-dione isolated from a fungus (21), which served as a lead compound for developing a series of more potent aromatic analogues (22). These discoveries were soon followed by others, resulting in a chemical variety of reported influenza virus endonuclease inhibitors, e.g., N-hydroxamic acid and N-hydroxyimide compounds (23), tetramic acid series and diketobutanoates (24), polyphenolic catechins (25), phenethylphenylphthalimide analogs derived from thalidomide (26), macrocyclic bisbibenzyls (27), a group of compounds bearing distinct pharmacophoric fragments (28), and 3-hydroxyquinolin-2(1H)-ones (29). An effort was also made to define the essential pharmacophore from the available structure-activity relationship (24).…”
mentioning
confidence: 99%
“…The endonuclease activity of the N-terminus of PA, which has a highly conserved sequence and has an essential function for influenza virus transcription and multiplication, has been identified as a potential target for developing novel anti-influenza virus drug (19) with low susceptibility to viral resistance. We demonstrate here that several Kampo medicines including Kakkonto, Shosaikoto, Saikokeishito, Keishito, Maobushisaishinto, and Maoto are able to inhibit recombinant PA endonuclease activity, whereas Kampo medicine Chikujountanto at a highest tested concentration of 100 μg/mL is unable to inhibit the enzyme activity.…”
Section: Resultsmentioning
confidence: 99%